2011
DOI: 10.3109/08923973.2011.591800
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the skin sensitization potential of chemicals in THP-1/keratinocyte co-cultures

Abstract: Many attempts have been made to develop in vitro sensitization tests that employ dendritic cells (DCs), DC-like cell lines or keratinocytes. The aim of the present investigation was to establish a co-culture of THP-1 cells and keratinocytes for evaluation of skin sensitization potential of chemicals. Co-cultures were constructed by THP-1 cells cultured in lower compartments and keratinocytes cultured in upper compartments of cell culture inserts. After 24 h exposure to sensitizers (2, 4-dinitrochlorobenzene, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…This conclusion has since been challenged, on the basis of misinterpretation of these clinical tests owing to the strong irritant potential of this substance . BC is therefore commonly used in studies as an irritant non‐sensitizer . However, recent studies have shown that the BC could, in fact, be a contact sensitizer .…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion has since been challenged, on the basis of misinterpretation of these clinical tests owing to the strong irritant potential of this substance . BC is therefore commonly used in studies as an irritant non‐sensitizer . However, recent studies have shown that the BC could, in fact, be a contact sensitizer .…”
Section: Discussionmentioning
confidence: 99%
“…Xenobiotics strongly sensitizing skin such as formaldehyde, eugenol, or dinitrochlorobenzene elicit the skin’s defences through Nrf2 activation. As a result of covalent links between these compounds and the cysteine residues in Keap1, Nrf2 dissociates from Nrf2-Keap1-Cul3 complex and consequently begins the ARE-dependent gene expression [ 10 , 78 ]. Many chemopreventive phytochemicals are known to activate Nrf2 either by oxidative or covalent modification of its cytosolic repressor—Keap1 or by phosphorylation of Nrf2 [ 15 ].…”
Section: Extracellular Nrf2 Activators In Keratinocytesmentioning
confidence: 99%
“…The use of animal-derived trypsin was clearly described in only one of the 50 methods to assess DC response, in which it was used to dissociate keratinocytes from foreskin. 112 As the trypsin manufacturer (Invitrogen Corp., now ThermoFisher Scientific) was mentioned in this case, it was possible to identify its porcine origin. Whenever trypsin was used for the isolation of cells from epidermal human or animal skin, 50,51 or for subculturing primary human keratinocytes or keratinocyte lineages in co-culture with DCs, 111,112 most of the analysed methods did not state the source or the manufacturer.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one experimental study involved the use of bovine pituitary extract, BSA, goat serum, dried skimmed milk and antibodies. 141 In some cases, the origin of the products was unclear: for instance, Cao et al 112 mentioned the use of a human keratinocyte growth supplement, which, after checking the manufacturer’s website, was found to include animal-derived bovine pituitary extract and transferrin.…”
Section: Discussionmentioning
confidence: 99%